Socialisation Determining Individual Financial Decisions from the Aspect of Financial Literacy - Csiszárik-Kocsir, Ágnes (Public Finance Quarterly, 2022)
Conscious financial decision-making and functioning is a set of learned elements that are not primarily taught in school. Much of financial behaviour is the result of a socialisation process, the primary arena for which is the family and the individual’s immediate environment. The aim of this paper is to examine the specific arenas of financial literacy and financial socialisation, as well as the impact of the latter on subsequent financial decision-making based on the results of a questionnaire survey. The study seeks to answer the question what foundations of trust financial socialisation creates in individuals, or who the primary actors are on whose advice individuals rely when making their own financial decisions. Using a cross-sectional analysis of the partial results of the questionnaire survey involving 3,515 individuals in 2022 presented in this paper, it is demonstrated that reliance on parents’ help is strong when it comes to making financial decisions. While this result varies from generation to generation due to life circumstances, the importance of parental background is clear for younger respondents. There is also evidence that corporate financial socialisation - and hence subsequent counselling - is more important than the school setting, which calls for a stronger emphasis on financial education in schools. It was also found that the survey respondents do not consider the internet as a credible source of advice at all, which reinforces their financial awareness.